The Intra-Manufacture Diameter Variability of Rotary Files and Their Corresponding Gutta-Percha Cones Using Laser Scan Micrometer - Mirmohammadi, Hesam; Sitarz, Monika; Shemesh, Hagay (Iranian Endodontic Journal, 2018)
Introduction: As an attempt to simplify the obturation process and create a tight seal, manufacturers offer gutta-percha (GP) cones matching different sizes of endodontic files. The purpose of this study was to evaluate whether intra-manufacture GP diameters matched the diameters of their corresponding files at different horizontal levels of the canal. Methods and Materials: Twenty files and corresponding GP master cones of Reciproc R 40/0.08 (VDW, Munich, Germany), WaveOne Large (40/0.08) (Dentsply Maillefer, Ballaigues, Switzerland), ProTaper F3 (30/0.09) (Dentsply Maillefer, Ballaigues, Switzerland), and Mtwo (40/0.06) (VDW, Munich, Germany) were examined using laser micrometer (LSM 6000 by Mitutoyo, Japan) with accuracy of 1 nm to establish their actual diameter at D0, D1, D3 and D6. Data were analysed using the independent t-test. The differences were considered as significant for P<0.05. Results: The diameter of GP master cones was significantly larger than the corresponding files at all levels with all the above brands. ProTaper GP diameter were closest to the file diameter at D1 (GP=0.35, File=0.35 mm), and D3 (GP=0.48, file=0.49). Conclusion: This in vitro study showed that within the same manufacturer GP cone diameters do not match the diameters of their corresponding files. Keywords: Diameter; Gutta-percha Cone; Laser Scan Micrometer; Rotary File; Taper